The Use of Microsoft Excel Application for Administrative Employees at the Ministry of Religion in Gowa - Andi Nur Resky; Muhammad Tahir; Seny Luhriyani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
The aim of this research was to discover the perception of administrative employees at the Ministry of Religion in Gowa regarding the use of the Microsoft Excel application, as well as the types of work that use Microsoft Excel and how the data or work is processed using Microsoft Excel at the Ministry of Religion in Gowa. The research method used is a descriptive qualitative method with data collection through interviews and data analysis carried out through data collection, data condensation, data presentation, and conclusion/verification steps. The results show that the majority of administrative employees of the Ministry of Religion in Gowa have a positive perception of the use of the Microsoft Excel application. The Ministry of Religion affairs employees acknowledges that the Microsoft Excel application helps in completing administrative tasks, especially in employee data management. Work that is commonly done with Excel includes grouping data, making calculations, processing documents, and making attendance lists, and policies. In the Diniyah Education and Islamic Boarding Schools (PD Pontren) field, Excel is used to process letters and received documents, check and classify data, and type Excel formulas. The processed data is sent through the WA application (WhatsApp), the Kemenag website, or the institution's email due to changes in flow caused by the pandemic. Based on these results, the Microsoft Excel application is very helpful for employees to complete their work with better effectiveness and efficiency. However, there are still difficulties and mistakes in using formulas and functions, especially for those who are less familiar with Excel. Some employees still need further information on how to use this application. Therefore, training or further introduction to the Microsoft Excel application is needed to improve the skills and administrative performance of employees in the Ministry of Religion affairs in Gowa. It is suggested that the Ministry of Religion affairs in Gowa provide facilities to improve computerization, especially in the use of Microsoft Excel, and hold training programs to help employees improve their skills in using the software.Keywords— Microsoft Excel, Administration, Data Processing, Perception